How to stop worrying and start living - Carnegie, Dale (New Delhi Prabhat, 2018)
It is divided into few sections such as how to eliminate fifty-percent of business worries immediately, avoid fatigue and keep looking young, reduce financial worries.
Keywords: Worry; Success